"At once sensible and imaginative": the essays of Mary Butts. Issue 2 (4th May 2019) - Hawkes, Joel
ABSTRACT: This paper is a critical introduction to the essays of British modernist author Mary Butts (1890–1937). Her essays explore the upheaval and trauma of the early twentieth century, expressing Butts's concerns about being disinherited from the land and her concomitant hope for the freedoms the new century might offer, especially for women. In the five essays presented and discussed, Butts avails herself of the form of the book review to generate feminist meditations on subjects that fascinated her, reflecting on her vision of a modern woman, what she is and what she might become. Butts's Collected Essays is published by McPherson & Co. later this year.